Cytotoxicity and genotoxicity of mahanimbine and girinimbine, pure compounds from murraya koeniggi on acanthamoeba spp. and human corneal epithelial cell line - Fatimah Hashim (Fakulti Sains dan Teknologi, 2012)
Mahanimbine (MH) and girinimbine (GR) are two carbazole alkaloids isolated from a local plant species, Murraya koenigii of the Rutaceae family. Both compounds have been shown to have insecticidal, antimicrobial, antifungal and anticancer properties.